Theory Building, Replication, and Behavioral Priming: Where Do We Need to Go From Here?. (May 2015) - Locke, Edwin A.
This article suggests that the field of behavioral priming, which is basically a technique, is in need of theory building. Guidelines from successful theory building by induction in the realm of conscious motivation (namely, goal setting and self-efficacy) are suggested. The process would include replication with variation, identifying the logical relation between a given prime and the action in question, discovering moderators and mediators, and clarifying the relationship between the conscious mind and the subconscious.